URGENSI PUTUSAN SELA BERKAITAN DENGAN HARTA KEKAYAAN PELAKU USAHA DALAM HUKUM ACARA PERSAINGAN USAHA DI INDONESIA - Marzuki, Al Araf Assadallah (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
In 2008, there was a case that made KPPU disappointed, namely the case of Temasek which Singapore Technologies Telemedia Pte Ltd (STT) sold 40.8% of its shares in PT Indosat Tbk to Qatar Telecom QSC (Qtel) through the acquisition of Asia Mobile Holdings Pte Ltd (AMH) in the midst of the cassation remedy process, which exceeds the stipulated provisions to transfer its ownership of shares. There are 3 reasons why interlocutory judgment is urgent, which are (1) Judging the abuse of dominant position by Temasek group on the sale of Indosat shares to Qatar Telecommunication in the middle The Supreme Court's process of legal remedies, creates uncertainty of KPPU's and District Court's verdict which ignored by Temasek business group by violating article 27 letter (a) Anti – Monopoli Act. (2) Judging from the objective of the formulation of the Anti – Monopoli Act particularly , that the regulation of abuse of dominant position is given on the basis to protect business competition and the public interest. (3). Judging from the economic aspect, the interlocutory judgement is useful to secure the assets of business actors who do not have good faith during the proceeding process. There will be no economic losses.